1997
DOI: 10.1080/000368497327029
|View full text |Cite
|
Sign up to set email alerts
|

Transportation costs and product demand: wagering on parimutuel horse racing

Abstract: Parimutuel horse-race wagering is in many respects like any other economic good but it differs in one important way from a vast majority of them. Given the present market arrangement, this good cannot be transported to the consumer; instead the consumer must travel to the production site where the good is consumed as it is produced. Thus, transportation costs must play a crucial role in the demand decision for horse-race wagering. The consumers incur not only out-of-pocket expenses for travelling but also the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…price of wagering (win percent) number of tables games at the facility location of market area customers relative to the facility presence of government restrictions on betting limits and on boarding time limits location of the facility's market area customers relative to competing riverboats with betting limit restrictions Following earlier studies on parimutuel wagering demand (Gruen, 1976;Morgan and Vasche, 1979, 1982Suits, 1979;Thalheimer and Ali, 1992, 1995a, 1995bAli and Thalheimer, 1997), win percent (equivalent to takeout rate for parimutuel operations), the amount withheld from handle for revenue to the riverboat (racino), served as the price of wagering.…”
Section: Demand For Wageringmentioning
confidence: 98%
See 1 more Smart Citation
“…price of wagering (win percent) number of tables games at the facility location of market area customers relative to the facility presence of government restrictions on betting limits and on boarding time limits location of the facility's market area customers relative to competing riverboats with betting limit restrictions Following earlier studies on parimutuel wagering demand (Gruen, 1976;Morgan and Vasche, 1979, 1982Suits, 1979;Thalheimer and Ali, 1992, 1995a, 1995bAli and Thalheimer, 1997), win percent (equivalent to takeout rate for parimutuel operations), the amount withheld from handle for revenue to the riverboat (racino), served as the price of wagering.…”
Section: Demand For Wageringmentioning
confidence: 98%
“…The finding of elastic demand for wagering at relatively high win percentage has also been found in studies of demand for parimutuel horse race wagering. Among these studies are Ali and Thalheimer (1997), Gruen (1976), Vasche (1979, 1982), Suits (1979), and Thalheimer and Ali (1995aAli ( , 1995b. In these studies, takeout rate elasticities varied from À1.3 to À3.1.…”
Section: Model Estimation and Analysismentioning
confidence: 98%
“…We found seven studies that dealt directly with the issue of casinos cannibalizing horse racing and one study that dealt with the impacts of introducing casino games at the race tracks to create racinos (race tracks with casino games), four of which found substitution (Ali & Thalheimer, 1997;Ray, 2001;Thalheimer, 2012;Walker & Jackson, 2008). Evidence from New Jersey (Ali & Thalheimer, 1997) estimated that the level of cannibalization is about 32%, and a study on racinos (Thalheimer, 2012) estimated that pari-mutuel wagering fell by 16% after the introduction of casino table games at the venue.…”
Section: /4mentioning
confidence: 99%
“…Evidence from New Jersey (Ali & Thalheimer, 1997) estimated that the level of cannibalization is about 32%, and a study on racinos (Thalheimer, 2012) estimated that pari-mutuel wagering fell by 16% after the introduction of casino table games at the venue. Two studies found no impact (Prybylski, Felsenstein, Freeman, & Littlepage, 1998;Siegel & Anders, 2001), but the study by Prybylski et al (1998) concluded that there was no impact because the pari-mutuel industry financially benefits from riverboat casinos, not because casinos would not substitute for parimutuel markets.…”
Section: /4mentioning
confidence: 99%
“…Embedded in these rationales and in line with the existing literature, several studies also suggest that the social, demographic, geographic, and religious characteristics of a jurisdiction may also serve as potential predictors of adoption and, in particular, the amount of revenues, to the extent that they reflect demand or preferences for gambling (Ali and Thalheimer ; Clotfelter and Cook ; Filer, Moak, and Uze ; Martin and Yandle ; Mikesell ; Philander and Abarbanel ; Richard ; Thalheimer ; von Herrmann ). In what follows, we present our empirical model and discuss in greater detail the theoretical underpinnings of each of these factors as they relate to gambling adoption and revenues.…”
Section: Literature Reviewmentioning
confidence: 67%